2015
DOI: 10.3748/wjg.v21.i19.5823
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the IL-17/IL-23 axis to the pathogenesis of inflammatory bowel disease

Abstract: Inflammatory bowel diseases (IBDs) are chronic disorders of modern society, requiring management strategies aimed at prolonging an active life and establishing the exact etiology and pathogenesis. These idiopathic diseases have environmental, genetic, immunologic, inflammatory, and oxidative stress components. On the one hand, recent advances have shown that abnormal immune reactions against the microorganisms of the intestinal flora are responsible for the inflammation in genetically susceptible individuals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(79 citation statements)
references
References 50 publications
1
77
0
1
Order By: Relevance
“…127 It is also important to note that Th17 cells can produce both IL-22 and IL-17, with the latter also being associated with the IBD pathogenesis. 126 Moreover, a recent study demonstrated that IFN-γ/IL-17-coproducing CD4+ T-cells specifically enriched in the inflamed mucosal tissue of patients with IBD also showed high expression levels of However, data from mouse models support an important protective role of IL-22 in IBD. 35,129 In humans, a loss of the Th22 subset has been reported in the colon of patients with UC, 130 whereas IL-22 production by ILCs has been seen to be impaired in inflamed tissue of patients with CD; 58 increased production of IL-22BP, a negative regulator of IL-22 function, has also been observed in human IBD.…”
Section: Il-22 and Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…127 It is also important to note that Th17 cells can produce both IL-22 and IL-17, with the latter also being associated with the IBD pathogenesis. 126 Moreover, a recent study demonstrated that IFN-γ/IL-17-coproducing CD4+ T-cells specifically enriched in the inflamed mucosal tissue of patients with IBD also showed high expression levels of However, data from mouse models support an important protective role of IL-22 in IBD. 35,129 In humans, a loss of the Th22 subset has been reported in the colon of patients with UC, 130 whereas IL-22 production by ILCs has been seen to be impaired in inflamed tissue of patients with CD; 58 increased production of IL-22BP, a negative regulator of IL-22 function, has also been observed in human IBD.…”
Section: Il-22 and Ibdmentioning
confidence: 99%
“…Evidence supports a role of IL-22 in driving IBD, through its ability to function as a proinflammatory cytokine. [123][124][125] Certainly, IL-23, a potent inducer of IL-22 production, 4 has a key role, 126 with an expansion of IL-23-responsive ILCs observed in the context of IBD. 127 It is also important to note that Th17 cells can produce both IL-22 and IL-17, with the latter also being associated with the IBD pathogenesis.…”
Section: Il-22 and Ibdmentioning
confidence: 99%
“…The s1/i1/m1 genotype of vacA is strongly associated with precancerous and cancerous gastric diseases . In relation to host inflammatory response, genetic polymorphisms in genes encoding IL‐1β, IL‐1RA, CXCL‐8, tumor necrosis factor alpha (TNFα), IL‐10, IL‐17A, IL‐17F, and IL‐23R have been linked to severe gastroduodenal diseases and particularly to precancerous lesions, suggesting that variations in the inflammatory response to the chronic H. pylori infection directly impact the initiation and progression of gastric diseases …”
Section: Introductionmentioning
confidence: 99%
“…8,9 In relation to host inflammatory response, genetic polymorphisms in genes encoding IL-1β, IL-1RA, CXCL-8, tumor necrosis factor alpha (TNFα), IL-10, IL-17A, IL-17F, and IL-23R have been linked to severe gastroduodenal diseases and particularly to precancerous lesions, suggesting that variations in the inflammatory response to the chronic H. pylori infection directly impact the initiation and progression of gastric diseases. [10][11][12][13] Due to its central role in H. pylori infection, the intensity of inflammatory response has been proposed as an explanation for clinical outcome determinism. Inflammatory response to H. pylori infection has been widely explored in animal models and in vitro experiments using cancerous gastric cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Acquired immunity plays a vital role in UC pathogenesis, where in T helper cell-type (Th) 1 and Th2 immune responses, as well as alternate subsets of T cells, such as regulatory T cells (Treg) and T helper 17 (Th17) cells, contribute to IBD[4,5]. …”
Section: Introductionmentioning
confidence: 99%